An Arduino-Based Autonomous Serving Robot with GPS Navigation for Cost-Effective Service Automation - Abhinav Kumar (International Journal of Robotics and Automation in Mechanics, 2026)
Robots built for service are no longer confined to research labs or luxury hotels; they are starting to appear in everyday spaces where speed and consistency make a real difference. In a restaurant, for example, a robot that can deliver meals and clear trays reduces staff workload, while in hospitals it can free nurses from routine errands. Schools, too, can benefit by using such machines for both practical and teaching purposes.In this study, we developed and tested a compact, low-cost serving robot intended for these very environments. The design relied on an Arduino controller as the central unit and used a PVC pipe frame to keep the structure both light and strong. Servo motors, DC motors, and a GPS module were added to handle movement and navigation. Building the system required mechanical assembly, circuit integration, and several cycles of programming and adjustment—“trial and error, as any engineer would admit, was part of the process.” When tested, the robot performed reliably: it completed more than 93 percent of its delivery tasks, carried up to 1.2 kilograms without tipping, and ran for over two hours on a single charge. These results show that a straightforward, modular approach can deliver a working solution at a fraction of the cost of commercial robots. More importantly, it demonstrates that service automation can be made accessible even to small institutions with limited budgets.
Keywords: Arduino-based control; Autonomous serving robot; GPS navigation system; Low-cost modular design; service robotics